Ministry of Defense and Military Production Decree No. 256 of the year 2021 On Amending Certain Provisions of the Statute of the National Authority for The Development of The Sinai Peninsula, Promulgated by Prime Minister Decree No. 915 of the Year 2012 = وزارة الدفاع والإنتاج الحربى قرار رقم 256 لسنة 2021 بشأن تعديل بعض أحكام النظام الأساسى للجهاز الوطنى لتنمية شبه جزيرة سيناء الصادر بقرار رئيس مجلس الوزراء رقم 915 لسنة 2012 - The Middle East Library for Economic Services (The Middle East Library fMinistry of Defense and Military Production Decree No. 256 of the year 2021 On Amending Certain Provisions of the Statute of the National Authority for The Development of The Sinai Peninsula, Promulgated by Prime Minister Decree No. 915 of the Year 2012 or Economic Services, 2025)
English & Arabic